A region-based video coding method for remote monitoring of neurosurgery - Xu, J.; Sclabassi, R.J.; Liu, Q.; Hu, C.; Chaparro, L.F.; Sun, M. (Proceedings of the IEEE 31st Annual Northeast Bioengineering Conference, 2005, 2005)
Transmitting high-quality neurophysiology video via the Internet is a challenging problem in telemedicine. We propose a novel content-selective video data processing and compression method based on the discrete wavelet transform (DWT). Our algorithm is adaptive to intraoperative monitoring video data and has a great scalability on real-time network bandwidth allocation. When compared with the general-purpose video compression methods, our method offers higher quality within the critical field of neurosurgical video.